Does board gender diversity affect firm performance? Empirical evidence from Thailand - Ravi Lonkani (2018)
© Serials Publications Pvt. Ltd. Theoretically, female representation has been predicted to affect financial firm performance in both positive and negative directions. While most studies investigate the relationship between female diversity of board and firm performance in western markets, this study focuses on the evidence from Thailand, where women live in a different sociocultural environment from their Anglo-American counterparts. Results indicate that performances and risks of firms having a female on CEO are not different from firms whose CEO are male. We find that percentages of femaleson the board are significant and positive in relation to a firms' performance. This finding underscores the 'monitoring role' stereotype of women but supports the 'advisory role' ideal of Asian business women. Further, the results show that the percentage of female directors are associated with a firms' profitability but has no relationship with any market risks.